The mechanical, thermo-physical and ultrasonic properties of scandium nitride in B1 and B2 phases - SINGH, ANURAG; Jyoti Bala; Devraj Singh; Singh, Shakti (Vietnam Journal of Science and Technology, 2025)
The mechanical, elastic, thermophysical and nonlinear ultrasonic effect of scandium nitride (ScN) were studied in B1 and B2 both phases at 300K. The working out of the second- and third-order elastic constants (SOECs and TOECs) for ScN were done by using Coulomb and Born-Mayer potential model. The mechanical properties were calculated with the help of SOECs using Voigt–Reuss–Hill approximation. The nonlinear ultrasonic velocities, Debye average velocity and Debye temperature were evaluated with the calculated values of SOECs. The thermophysical properties of ScN were computed along <100>, <110> and <111> crystallographic orientations. Finally, the ultrasonic attenuation along suitable crystallographic direction was calculated in ScN at 300K. The acquired results were compared and discussed with existing findings of the ScN in B1 and B2 both phases.